Bargaining Between Retailers and their Suppliers. - Thanassoulis, J; Smith, H (OUP, 2009)
This chapter surveys new research concerning bargaining within supply chains and its implications for buyer power. The paper explores the implications of the research on supermarket supply chains for primary, secondary and private-label branded goods. The empirical base in support of the theories is also discussed.